A SURVEY OF LITIGATION REFORMS AS A CATALYST TO CHECK PERPETRATORS OF CHILD SEXUAL ABUSE IN SOUTH-SOUTH, NIGERIA TO DETER SEX ABUSE OF CHILDREN (International Journal of Functional Research in Arts and Humanities (IJFRAH), 2024)
Child Sexual Abuse (CSA) is one of the prevalent problems in the global world. It is an all- encompassing communal and collective distress that can affect members of the society directly or indirectly, and particularly, the victims’ welfare and efficiency throughout their existence. Thus, this study investigated the socio-cultural context of child sexual abuse and identified the coping strategies adopted by the victims of child sexual abuse in South-South, Nigeria. Primary data were adopted for this study. Information were sourced using both questionnaire and interview  tools.  1012  respondents,  who  were  adolescents  (Senior  Secondary  School  students  of  11-18 years)  and  adult  police  officers,  non-governmental  organization  workers  and  health  professionals,  were engaged in the study area.  Majority  (59.7%)  of  which  were  female,  while  male  respondents  accounted  for  40.3%.  Both descriptive and inference techniques were employed to analyse the data. The findings revealed that 85.3% of  the  respondents  stated  that  their  culture  does  not  allow/permit  child  marriage.  Also,  69.6%  of  the respondents affirmed that their culture allows the practice of polygamy family system. However, 15.3% of the respondents stated that polygamy is not fostered by their culture. Also, from the table, the majority of the respondents going by 65.7% stated that their culture frown at child marriage, while another majority going by 89.7  % stated that their culture allows/permit  premarital sex.  The coping strategies adopted significantly influence the victims of child sexual abuse (child support institution/hospital/rehabilitation center, receiving counseling from parent/guardian, counseling and routine checkups, and rehabilitation activities, physical and emotional support). This study recommends enlightening initiatives in schools, religious centers and homes  with a view to impacting the children with skills and knowledge to help them recognize unsafe situation and prevent sexual abuse such as identifying limit violations, superfluous forms of touching and how to beckon or call for help. Also, there should be concentrated impact of post-disclosure events on victims – the investigation, justice processes and publicity. In addition, government should lead on securing better and more consistent support for victims of child sexual abuse through entire court processes and beyond into therapeutic support for victims of child sexual abuse.